Attenuation of hyperoxia-induced lung injury in neonatal rats by 1α, 25-Dihydroxyvitamin D3. (1st August 2015) - Chen, Yan; Li, Qiong; Liu, Yalan; Shu, Li; Wang, Na; Wu, Yipin; Sun, Xue; Wang, Lin
ABSTRACT Background: Mounting evidence suggests that Toll-like receptor (TLRs) plays an important role in oxidative stress and is implicated in the pathogenesis of hyperoxic lung injury. 1α, 25-Dihydroxyvitamin D3 (1, 25(OH)2D3), the hormonally active form of vitamin D, not only plays an essential role in mineral balance, but also possesses immunomodulatory and antioxidant properties. Besides, Vitamin D3 is involved in the regulation of TLRs signaling. The present study was designed to investigate whether 1, 25(OH)2D3 attenuates hyperoxia-induced lung injury by regulating TLRs signaling in neonatal rats. Methods: Pups were divided into four groups: normoxia control group (NC), normoxia plus 1, 25(OH)2D3 treatment group (ND), hyperoxia control group (HC), and hyperoxia plus 1, 25(OH)2D3 treatment group (HD). Lung tissues were collected for histological examination and detection of mRNA and protein expressions. Results: Treatment of hyperoxia-exposed animals with 1, 25(OH)2D3 resulted in significantly increased body weight and reduced hyperoxia-induced lung injury. Moreover, 1, 25(OH)2D3 significantly downregulated the expression of TLR4, NF-κB, and the inflammatory cytokines TNF-α, IL-1β, and IL-6. Conclusions: 1, 25(OH)2D3 could attenuate hyperoxia-induced lung injury in neonatal rats, possibly by regulating TLR4/NF-κB signaling.